La enseñanza del Derecho en la Universidad de Buenos Aires : propuesta de investigación desde una perspectiva antropológica - Fischman, Fernando (2009)
"Paper presented at the 8th National Congress of Legal Sociology "Law, Democracy and Society", held on November 22, 23 and 24, 2007 at the Faculty of Legal and Social Sciences, National University of Rosario, Santa Fe, Argentina."